"Ihuprevotella massiliensis" gen. nov., sp. nov., isolated from human gut. (November 2016) - Ricaboni, D.; Mailhe, M.; Benezech, A.; Fournier, P.E.; Raoult, D.; Khelaifia, S.
Abstract: We report here the main characteristics of "Ihuprevotella massiliensis" strain Marseille-P2826 T (CSURP 2826) that was isolated from a human right colon lavage sample.